Antiviral response and immunopathogenesis of interleukin 27 in COVID-19 (2023)
ABSTRACT: The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is associated with a high mortality rate. The clinical course is attributed to the severity of pneumonia and systemic complications. In COVID-19 patients and murine models of SARS-CoV-2 infection, the disease may be accompanied by excessive production of cytokines, leading to an accumulation of immune cells in affected organs such as lungs. Previous reports have shown that SARS-CoV-2 infection antagonizes interferon (IFN)-dependent antiviral response, thereby preventing the expression of IFN-stimulated genes (ISGs). Lower IFN levels have been linked to more-severe COVID-19. Interleukin 27 (IL27) is a heterodimeric cytokine composed of IL27p28 and EBI3 subunits, which induce both pro- and anti-inflammatory responses. Recently, we and others have reported that IL27 also induces a strong antiviral response in an IFN-independent manner. Here, we investigated transcription levels of both IL27 subunits in COVID-19 patients. The results show that SARS-CoV-2 infection modulates TLR1/2-MyD88 signaling in PBMCs and monocytes and induces NF-κB activation and expression of NF-κB-target genes that are dependent on a robust pro-inflammatory response, including EBI3; and activates IRF1 signaling which induces IL27p28 mRNA expression. The results suggest that IL27 induces a robust STAT1-dependent pro-inflammatory and antiviral response in an IFN-independent manner in COVID-derived PBMCs and monocytes as a function of a severe clinical course of COVID-19. Similar results were observed in macrophages stimulated with the SARS-CoV-2 spike protein. Thus, IL27 can trigger an antiviral response in the host, suggesting the possibility of novel therapeutics against SARS-CoV-2 infection in humans.